Introduction to the special issue: Historical and contemporary perspectives on educational evaluation - Anderson, Lorin W.; de Ibarrola, Maria; Phillips, D. C. (Education Policy Analysis Archives, 2018)
Most special issues on evaluation focus on one form or type of evaluation (e.g., program evaluation, personnel evaluation, and, increasingly, educational system evaluation. This special issue is unique in that there are papers on system evaluation, program evaluation, teacher evaluation, and student evaluation. Some papers are primarily conceptual, others are empirical, and still others are a little of each. Some papers are more historical, some contemporary, and some a little of each. The authors represent four countries: Canada, Mexico, South Africa, and the United States, providing an international perspective on key issues. The final paper contains six recommendations concerning the future of educational evaluation based on an analysis of commonalities across the papers.